Sesquiterpene volatile organic compounds (VOCs) are markers of elicitation by sulfated laminarine in grapevine - Chalal, Malik; Winkler, Jana B.; Gourrat, Karine; Trouvelot, Sophie; Adrian, Marielle; Schnitzler, Jörg-Peter; Jamois, Frank; Daire, Xavier (Frontiers in Plant Science, 2015)
Inducing resistance in plants by application of elicitors of defense reactions is an attractive plant protection strategy, especially for grapevine (Vitis vinifera) which is susceptible to severe fungal diseases. Though induced resistance (IR) can be successful in controlled conditions, under outdoor conditions IR is in most cases not effective enough for practical disease control. Progress in the application of IR requires a better understanding of grapevine defense mechanisms and the ability to monitor defense markers in order to identify factors (physiological, environmental…) that can impact IR in the vineyard. Volatile organic compounds (VOCs) are well-known plant defenses compounds that have only received little or no attention in the case of grape-pathogen interactions to date. This prompted us to investigate whether an elicitor, the sulfated laminarin (PS3), actually induces the production of VOCs in grapevine. Online analysis (PTR-QMS) of VOC emissions in dynamic cuvettes and passive sampling in gas tight bags with solid phase micro extraction (SPME-GC-MS) under greenhouse conditions showed that PS3 elicited emission of VOCs. Some of them (as (E,E)-α-farnesene) might be good candidates as biomarkers of elicitor-IR whereas methyl salicylate appears to be rather a biomarker of downy mildew infection. A negative correlation between VOC emission and disease severity suggests a positive role of VOCs in grape defense against diseases.